A construção de tesauros com a integração de procedimentos terminográficos - Cervantes, Brígida Maria Nogueira [UNESP] (2009)
It investigates the terminographic integration for the thesauri construction in the search of terminographic procedures that may be used together with existing methodological procedures of subject analysis, for the improvement of the concepts representation in the thesauri construction. It is a theoretical-methodological study of the thesauri construction, focusing in the concepts identification in specialized area for the representation and thematic information retrieval. The general purpose of this research is to conceive a methodological model for the thesauri construction with the terminographic procedures integration. The specific purposes are to analyze and synthesize theoretical-methodological framework on thesauri construction, identify the main theoretical-methodological aspects of Terminology/Terminography which contribute to the thesauri construction, and present a proposal of a terminographic methodological model for the thesaurus construction. The research methodology is bibliographical, descriptive and exploratory, focusing on the thematic approach of vocabulary of speciality areas. It emphasizes as a result of this work, the “Preliminary Terminographic Thesauri in Information Management”, available in the web. It concludes that the improvement of thesauri construction stages, with the contributions of terminographic procedures, produce a concepts representation, by means of terms, having in mind the acquisition of a consistent vocabulary, which forms the basis for the organization and thematic information retrieval, and compatible with the demand of specialized areas.